Analisis Kompetensi Profesional Guru MI Dalam Menghadapi Gen Alpha: Sebuah Tinjauan Literatur - Nur Shofiyyur Rohmah; Novel Aditya Rahman; Munawir (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
Generation Alpha, born after 2010, has unique traits as digital natives. They need a different educational system. However, in the Madrasah Ibtidaiyah (MI) setting, there is a significant gap between students' visual-interactive learning styles and the traditional teaching skills of teachers. Objective: This study aims to look at the learning style traits of generation Alpha, pinpoint the challenges MI teachers face, and create a relevant teacher competency framework for the digital age. Methods: This research uses a qualitative approach through library research, combining various sources related to generation Alpha education and TPACK competency. Results: The findings show that generation Alpha prefers visual learning, has a short attention span, and can multitask, but they are also at risk for character decline and low social empathy. The main challenges for MI teachers include limited digital skills, inadequate infrastructure, and heavy administrative tasks. As a solution, a teacher competency framework was developed, combining Technological Pedagogical Content Knowledge (TPACK), Social Constructivism Theory, and the reinforcement of Islamic moral values. Conclusion: Changing teachers from traditional instructors to digital facilitators, who also provide spiritual guidance (digital parenting), is crucial for successful education in today's Madrasah Ibtidaiyah.